Rotation analysis of teams' performances at 2003 youth European volleyball championship - Durkovic, T.; Marelic, N.; Resetar, T. (Kinesiology, 2009)
The purpose of this study was to confirm the possible statistically significant differences between two groups of teams - the group of semi-finalists (1st-4th place), and other teams (5th-8th place), on the basis of 6 situational parameters (service, serve reception, block, defence, attack and counter?attack) in each of the 6 game rotations. A sample of 19 games played at the 2003 European Youth Volleyball Championship in Zagreb was used. The games were recorded and analysed by means of the "Data Volleyball" software. Each game was analysed for both participating teams. Canonical discriminant analysis (standard method) was employed to determine any possible differences. Discriminant functions showed significant differences between the two groups in rotations 5 and 3 (p<.01). In other rotations (1, 6, 4 and 2) there were no significant differences between these two groups. From the aspect of game complexes we can conclude that on the basis of the variable/phases of Complex II we can see the differences more clearly between the two groups. On the level of the game phases the variable service had the largest loadings across the discriminant functions, followed by the variables attack, block, and counter-attack. Service reception and defence had low loadings on the discriminant functions.